Marigold development in response to excess copper at different soil pH - de Carvalho Lacerda, Leandra; Swarowsky, Alexandre; Menegaes, Janine Farias [UNESP]; Backes, Fernanda Alice Antonello Londero; dos Santos Salazar, Rodrigo Fernando (Centro Universitario de Maringa, 2024)
Agricultural areas have been constantly contaminated by excessive applications of agricultural products, including copper (Cu), in wine-growing areas. Thus, seeking for a low environmental impact agriculture, the objective of this work was to evaluate the vegetative development of marigold (Tagetes patula L.) in response to excess of Cu at different pH levels in the soil. The experiment took place in the greenhouse using a completely randomized design, with a 5x2 factorial (added doses of Cu in the soil: 0 (no addition: control), 250, 500, 750 and 1,000 mg kg-1 of Cu and pH corrections in the soil: 5.5 and 6.0 according to the soil analysis report), with five repetitions. Phytotechnical parameters, nutrient content in dry mass, phytoremediation factors and Cu extraction rate in the plant were evaluated. It was found that marigold plants showed good growth and vegetative development at both soil pH levels, however, the Cu concentration increase in the soil negatively affected plant height. There was no evidence of phytotoxicity in the plants, so it was concluded that marigold plants are tolerant in areas containing high concentrations of Cu in the soil, without altering their ornamental characteristics.
Desenvolvimento de tagetes em resposta ao excesso de cobre em diferentes pH no solo
Keywords: Low environmental impact agriculture; Tagetes patula L; Tolerance to copper in the soil, Floriculture